Backgrounds for Blondes - National Paint, Varnish (Pamphlets corresponding to radio shows produced by the National Paint, Varnish and Lacquer Association, 1940)
Booklet corresponding to a radio broadcast program created by the National Paint, Varnish, and Lacquer Association. The booklet discusses furniture made of blonde wood, and how to color one's walls and decorate a room to accent the furniture tone. Describes several rooms decorated to highlight blonde furniture for inspiration. Also provides instructions for refinishing wood furniture to give it a lighter tone. Includes small stylized illustrations throughout and decorated covers. The National Paint, Oil and Varnish Association, Inc. was formed in 1933 and was the national professional association representing all branches of the paint, oil, and varnish industries.
Keywords: Interior decoration; Paint materials; Linseed oil; Furniture finishing; Varnish and varnishing; Varnish industry; Paint industry and trade; Advertising--Paint